2010
DOI: 10.1152/physrev.00054.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Signaling in the Heart: Angels Versus Demons in a Heart-Breaking Tale

Abstract: Among the myriad of intra-cellular signaling networks that govern the cardiac development and pathogenesis, mitogen-activated protein kinases (MAPKs) are prominent players that have been the focus of extensive investigations in the past decades. The four best characterized MAPK subfamilies, ERK1/2, JNK, p38, and ERK5, are the targets of pharmacological and genetic manipulations to uncover their roles in cardiac development, function, and diseases. However, information reported in the literature from these effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
582
2
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(627 citation statements)
references
References 471 publications
(592 reference statements)
20
582
2
14
Order By: Relevance
“…Increased cell size was seen in neonatal rat cardiac myocytes with microinjection of an activated Ras mutant (34), overactivated JNK by constitutively active MKK7 (35), overactivated p38 by constitutively active MKK6 (33), and expression of constitutively active MEK1 (36). Although in vitro experiments show pro-hypertrophic effects for JNK, MEK1/2, and p38, in vivo experiments have generated more conflicting results (37). Additional studies are needed to conclusively show the relative contributions of these ligands to various cardiac hypertrophy phenotypes in myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cell size was seen in neonatal rat cardiac myocytes with microinjection of an activated Ras mutant (34), overactivated JNK by constitutively active MKK7 (35), overactivated p38 by constitutively active MKK6 (33), and expression of constitutively active MEK1 (36). Although in vitro experiments show pro-hypertrophic effects for JNK, MEK1/2, and p38, in vivo experiments have generated more conflicting results (37). Additional studies are needed to conclusively show the relative contributions of these ligands to various cardiac hypertrophy phenotypes in myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have revealed crucial proteins and pathways involved in the process of cardiac hypertrophy, including the mitogen‐activated protein kinase (MAPK)3 and phosphatidylinositol 3 kinase–AKT–mammalian target of rapamycin (mTOR)4, 5, 6 signaling pathways, the underlying mechanism of cardiac hypertrophy remains elusive. Recently, numerous studies have reported the effects of immunologic molecules in cardiac hypertrophy 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Like atRA, mitogen-activated protein kinases (MAPK) play an essential role in cell proliferation and differentiation [16][17][18][19][20]. These kinases are components of signaling cascades that relay extracellular stimuli to transcription factors in the nucleus.…”
Section: Stem Cells and Developmentmentioning
confidence: 99%
“…ERK activity is required for adipogenesis [30][31][32][33], but its influence in myogenesis is uncertain. Indeed, ERK was either judged to be unnecessary or necessary to myogenic differentiation [20,23,24]. Overall, those studies relied on different cell differentiation protocols to induce adipogenesis and myogenesis, preventing the unambiguous determination of the extent to which ERK and p38 influence undifferentiated cells to become adipocytes or myocytes.…”
Section: Stem Cells and Developmentmentioning
confidence: 99%
See 1 more Smart Citation